Pharmacodynamic Evaluation and PK/PD-Based Dose Prediction of Tulathromycin: A Potential New Indication for Streptococcus suis Infection - Yu-Feng Zhou; Yu-Feng Zhou; Hui-Min Peng; Hui-Min Peng; Ming-Xiao Bu; Ming-Xiao Bu; Ya-Hong Liu; Ya-Hong Liu; Jian Sun; Jian Sun; Xiao-Ping Liao; Xiao-Ping Liao (Frontiers Media S.A., 2017)
Tulathromycin is the first member of the triamilide antimicrobial drugs that has been registered in more than 30 countries. The goal of this study is to provide a potential new indication of tulathromycin for Streptococcus suis infections. We investigated the pharmacokinetic and ex vivo pharmacodynamics of tulathromycin against experimental S. suis infection in piglets. Tulathromycin demonstrated a relatively long elimination half-life (74.1 h) and a mean residence time of 97.6 h after a single intramuscular administration. The minimal inhibitory concentration (MIC) and bactericidal concentration in serum were markedly lower than those in broth culture, with Mueller-Hinton broth/serum ratios of 40.3 and 11.4, respectively. The post-antibiotic effects were at 1.27 h (1× MIC) and 2.03 h (4× MIC) and the post-antibiotic sub-MIC effect values ranged from 2.47 to 3.10 h. The ratio of the area under the concentration-time curve divided by the MIC (AUC/MIC) correlated well with the ex vivo antimicrobial effectiveness of tulathromycin (R2 = 0.9711). The calculated AUC12h/MIC ratios in serum required to produce the net bacterial stasis, 1-log10 and 2-log10 killing activities were 9.62, 18.9, and 32.7, respectively. Based on the results of Monte Carlo simulation, a dosage regimen of 3.56 mg/kg tulathromycin was estimated to be effective, achieving for a bacteriostatic activity against S. suis infection over 5 days period. Tulathromycin may become a potential option for the treatment of S. suis infections.